Avaliação da educação ambiental e proposta de integração do tema “praia” na educação básica no município de Vila Velha, ES - Araujo, Renato Ferreira de (2019)
The municipality of Vila Velha (ES) is coastal, it has over 32 km of beaches that are widely used by residents and tourists. Beaches are an important space / place for social interaction, recreation and sports in the city. However, despite the relevance of the beach to the city, this unique physiographic unit has not been contemplated by school geography and education projects. environmental. It is important to know that the beaches, besides being a space of use, also play an environmental role: they act by dissipating the incident energy and protect the coast against the erosive action of the sea and in high energy situations, such as meteorological tides. For example, there is a rise in mean sea level at the local level that creates disruption to coastal cities. This study aimed to elaborate an Environmental Education project that integrates the theme beach in basic education from information gathered about environmental education and the beaches of the municipality. This information was collected by conducting interviews, applying questionnaires, consulting scientific articles and cartographic material about the city of Vila Velha as well as field visits to the city's beaches. The information gathered in the research showed that: students have a habit of going to the beach, teachers have a good acceptance of the subject to be developed in geography classes, there is a need to complement students' basic knowledge about the coastal environment and textbooks used in the municipality practically do not address the subject. After analyzing the information collected about environmental education and the physical and use characteristics of the beaches of the city of Vila Velha, it was decided to elaborate a project containing a didactic pedagogical production with suggestions of activities for the teacher to develop the beach theme. in geography classes in municipal basic education.